Second language pragmatic appropriateness in telecollaboration: The influence of discourse management and grammaticality. (February 2017) - Cunningham, D. Joseph
Abstract: Context-specific enactment of pragmatic appropriateness requires high levels of second language (L2) pragmalinguistic and sociopragmatic knowledge. In order to elucidate the appropriateness of request production in telecollaboration for professional purposes, this study examines the role of grammaticality and discourse management in oral synchronous interactions between L1 and L2 speakers of German. Findings indicate that ungrammaticality and lack of discourse control impeded the appropriateness of the learners' interaction with L1 speakers. Conversely, those learners displaying higher levels of grammaticality and more attention to discourse-level organization were able to produce more appropriate requests. To conclude, empirical findings are discussed in relation to pedagogical implications.